2022
DOI: 10.1002/jmv.27734
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2, SARS‐CoV, and MERS‐CoV encode circular RNAs of spliceosome‐independent origin

Abstract: Circular RNAs (circRNAs) are a newly recognized component of the transcriptome with critical roles in autoimmune diseases and viral pathogenesis. To address the importance of circRNA in RNA viral transcriptome, we systematically identified and characterized circRNAs encoded by the RNA genomes of betacoronaviruses using both bioinformatical and experimental approaches. We predicted 351, 224, and 2764 circRNAs derived from severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), SARS‐CoV, and Middle East re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…It is reported that two circRNAs are a significant component of coronavirus transcriptome because of having ORF3a and M and containing strong IRES signals. 121 It has also been observed that SARS-CoV-2, like the majority viruses, can change the expression of host circRNAs. Consequently, 42 of the total 6,118 circRNAs were remarkably dysregulated, of which 17 circRNAs were upregulated and 25 were downregulated upon SARS-CoV-2 infection at various phases.…”
Section: Circrnas In Sars-cov-2 Infectionmentioning
confidence: 99%
“…It is reported that two circRNAs are a significant component of coronavirus transcriptome because of having ORF3a and M and containing strong IRES signals. 121 It has also been observed that SARS-CoV-2, like the majority viruses, can change the expression of host circRNAs. Consequently, 42 of the total 6,118 circRNAs were remarkably dysregulated, of which 17 circRNAs were upregulated and 25 were downregulated upon SARS-CoV-2 infection at various phases.…”
Section: Circrnas In Sars-cov-2 Infectionmentioning
confidence: 99%
“…Yang S et al. ( 17 ) predicted 351, 224, and 2764 circRNAs derived from SARS-CoV-2, SARS-CoV, and Middle East respiratory syndrome coronavirus, respectively. Moreover, 75 potential SARS-CoV-2 circRNAs were identified from RNA samples extracted from SARS-CoV-2-infected Vero E6 cells.…”
Section: Pathogenesis Of Sars-cov-2 and Regulation Of Related Circrnasmentioning
confidence: 99%
“…In addition, a study by Yang S et al. ( 17 , 98 ) found that abundant and diverse circRNAs are generated by SARS-CoV-2, SARS-CoV and MERS-CoV and represent a novel type of circRNA that differs from circRNAs encoded by DNA genomes, and forward splice junctions (FSJs) representing noncanonical “splicing” events were detected in these circRNA genome sequences. Furthermore, the study also reported the existence of alternative back-splicing events in SARS-CoV-2 circRNAs that share either 5’ or 3’ breakpoints.…”
Section: Potential Mechanisms Of Circrnas In Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the most studied DNA viruses related to circRNAs are tumor viruses, including the Epstein Barr virus (EBV) ( 13 16 ), Kaposi Sarcoma herpesvirus (KSHV) ( 14 , 17 19 ), and human papillomaviruses (HPVs) ( 20 ). We recently reported that circRNAs are an important component of the transcriptome encoded by RNA viruses of the betacoronavirus genus of Coronaviridae, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), SARS-CoV, and Middle East respiratory syndrome (MERS-CoV) ( 21 ).…”
Section: Introductionmentioning
confidence: 99%